Changing reimbursement models and private equity ownership in spine surgery - Galetta, Matthew S.; Makanji, Heeren S.; Strony, John; Goyal, Dhruv K. C.; Kurd, Mark F. (Annals of Translational Medicine; Vol 7, Supplement 5 (September 10, 2019): Annals of Translational Medicine (Focus on: “Current Trends and Advancements in Spine Surgery”), 2019)
Rising costs of healthcare have been a problem in the United States in the past decade, with unnecessary strain on both providers and patients. The fee-for-service reimbursement model has been proposed as one of the biggest contributors to this phenomenon; as such, newer reimbursement model—including the bundled payments model—have been proposed and are becoming more widely adopted. This review will first discuss the current payment models in practice and then overview private equity ownership as a new avenue in this particular domain.